Diagnosis and Management of Unruptured Tubal Ectopic Pregnancy - Rudrakar, Ashwini Pundlik; Lewis , Preeti F.; Bavdekar , Nitin; Wagh , Ajinkya (Research Highlights in Disease and Health Research Vol. 9, 2023)
The present study aimed to analyse the age group, gravida , risk factors, clinical presentation, treatment given and outcome of the unruptured ectopic pregnancy. Tubal ectopic pregnancies remain a challenging and life-threatening obstetric condition in the early stages that unavoidably lead to abortion or rupture, further reflected by the associated maternal mortality. We studied 25 women admitted to our tertiary care hospital, through emergency or outpatient department with tubal ectopic pregnancy from January 2017 through September 2021. The most common risk factor is advanced maternal age (36%) followed by previous history of induced abortion in 24% cases and history of abdominal or pelvic surgery in 20% cases. The typical triad of amenorrhoea, pain abdomen and bleeding was observed in majority of cases. Significantly more number of cases had ampullary pregnancy (52%), followed by cornual (24%) and fimbrial (24%).Out of 25 cases of unruptured tubal ectopic pregnancies,68% cases were treated by purely surgical intervention while 8% cases were managed medically by methotrexate however in 24% cases, the medical treatment failed and they ended up having surgical intervention. Ectopic pregnancy occurs in around 1–5% of all pregnancies, and is associated with significant morbidity and mortality. Surgery will always have a role in the management of women with unruptured ectopic pregnancy who are acutely unwell or where medical management is unlikely to be, or has been unsuccessful.